2021
DOI: 10.1111/1751-7915.13821
|View full text |Cite
|
Sign up to set email alerts
|

Flexible integrated sensing platform for monitoring wound temperature and predicting infection

Abstract: Wound infection is a challenging clinical problem that imposes substantial economic and psychological burdens on patients. However, the wound covered by a dressing is in an 'unknown' state. Recently, researchers have focused on understanding the condition of the wound without removing the dressing. Here, we presented a flexible integrated sensing platform (FISP) that can monitor multiple indicators, including local temperature. The platform consists of a flexible sensor chip (FSC), a controlled printed circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Based on the data from the ultraviolet–visible spectrophotometry (Fig. S5 ), it was found that fibrinogen remained conformationally stable up to 42 °C, which is the maximum temperature of the chronic wound 47 49 . Since the first melting temperature (T m ) of the protein begins from about 59 °C, it is expected that the protein maintains its conformational stability when placed in the wound site.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the data from the ultraviolet–visible spectrophotometry (Fig. S5 ), it was found that fibrinogen remained conformationally stable up to 42 °C, which is the maximum temperature of the chronic wound 47 49 . Since the first melting temperature (T m ) of the protein begins from about 59 °C, it is expected that the protein maintains its conformational stability when placed in the wound site.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Zhang et al. [78] showed that wounds with P. aeruginosa and K. pneumoniae were about 37.5–38 °C, while wounds with S. aureus were 38.5 °C.…”
Section: Wound Biofilm Detectionmentioning
confidence: 99%
“…[77] Furthermore,h igher local wound temperatures were associated with ag reater risk for Gram-positive infection. Fori nstance,Z hang et al [78] showed that wounds with P. aeruginosa and K. pneumoniae were about 37.5-38 8 8C, while wounds with S. aureus were 38.5 8 8C.…”
Section: Pyocyanina Nd Uric Acidmentioning
confidence: 99%